The strategic breakdown: CHAC enzymes as regulators of glutathione homeostasis and disease implications - Schröder, Emma; Jalilvand, Tida V.; Kahl, Janina; Kaiser, Charlotte S.; Liebau, Eva (Frontiers in Molecular Biosciences, 2025)
This review explores the critical function of the evolutionarily conserved ChaC-like enzyme family as central regulators of intracellular glutathione (GSH) homeostasis, focusing on the mammalian isoforms CHAC1 and CHAC2. We detail how these γ-glutamylcyclotransferases degrade GSH, thereby modulating cellular redox balance and integrating diverse stress signaling pathways. CHAC1 emerges as a key stress-responsive effector, transcriptionally upregulated via the ATF4-CHOP axis during endoplasmic reticulum stress and amino acid deprivation. Its role is especially crucial in the induction of ferroptosis, an iron-dependent cell death pathway, positioning it as a context-dependent modulator of cancer progression, neurotoxicity and neurodegeneration. Furthermore, we examine the opposing roles of CHAC1 and CHAC2 in stem cell fate decisions via NOTCH1 signaling and development. The complex duality of CHAC1 in oncology, acting as both a tumor suppressor by promoting ferroptosis and a potential oncogene in TP53-mutant backgrounds, alongside its functions in neuroprotection and immunity, underscores its therapeutic potential.